Gianotti-Crosti syndrome due to Epstein-Barr virus infection with possible role of palivizumab. - Azevedo, A.; Magalhães, M.; Rodrigues, J.; Martins, A.; Oliveira, T.; Machado, S. (European Journal of Pediatric Dermatology, 2015)
A 16 months old girl with a congenital atrial septal defect was admitted to our emergency department (ED) with a history of a “rash” in the last 7 days. There was no history of fever or preceding illness. However, she had undergone palivizumab passive immunization 2 weeks before the development of the first symptoms. Initially, the “rash” was characterized by symmetrical pink papules on the extensor surface of both legs. Five days later, the eruption affected the upper limbs with multiple, pruritic, red-violaceous papules coalescing into plaques on both lower extremities and elbows. Physical examination at ED showed 2 mm in size, confluent, symmetrical and monomorphic red-violaceous papules on the extensor surface of both legs, knees and elbows, sparing the trunk, palms and soles...